Initial Comparison Of Difference Of Type Warm Up Exercise On Pulmonary Function - Kim, Byung-seob; Park, Su-bin; Jeon, Nam-hyun; Lee, Dong-Yeop; Hong, Ji-Heon; Yu, Jae-Ho; Kim, Jin-seop (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to find out how passive and active pre-treadmill exercise affect pulmonary capacity.Method/Statistical analysis: This study was conducted with 20 healthy male university students in their 20s and they were randomly placed in each group. Spirometer (Pony FX, Italy), Ambu-bag (Mow Medical, Korea) and Ultrabreathe (Aqus, UK) were used. Comparisons were made between and inside groups.Findings: Compared with the group before and after, the mean value of active inspiratory muscle warm-up group decreased in all factors, but there were significant differences in maximal oxygen consumption(VO2max), expiratory minute volume(VE), metabolism(METs)(p.05). In comparison between the groups, the passive inspiratory muscle warm-up group increased no significantly in all items than the active inspiratory muscle warm-up group(p>.05).Improvements/Applications: Active inspiratory muscle warm-up exercise is thought to negative effects on some pulmonary function in a short time than active inspiratory muscle warm-up exercise.